2014
DOI: 10.1139/cjpp-2013-0498
|View full text |Cite
|
Sign up to set email alerts
|

Developmental determinants of cardiac sensitivity to hypoxia

Abstract: Cardiac sensitivity to oxygen deprivation changes significantly during ontogenetic development. However, the mechanisms for the higher tolerance of the immature heart, possibilities of protection, and the potential impact of perinatal hypoxia on cardiac tolerance to oxygen deprivation in adults have not yet been satisfactorily clarified. The hypoxic tolerance of an isolated rat heart showed a triphasic pattern: significant decrease from postnatal day 1 to 7, followed by increase to the weaning period, and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 93 publications
2
12
0
Order By: Relevance
“…However, intervention initiated within 12 h has beneficial effects (471). The sensitivity of neonatal hearts to I/R depends on age, with the immature myocardium being highly susceptible to ischemia (849), whereas enhanced tolerance is seen shortly thereafter (401, 563, 611, 642, 849). …”
Section: General Characteristics Of Ischemia/reperfusionmentioning
confidence: 99%
“…However, intervention initiated within 12 h has beneficial effects (471). The sensitivity of neonatal hearts to I/R depends on age, with the immature myocardium being highly susceptible to ischemia (849), whereas enhanced tolerance is seen shortly thereafter (401, 563, 611, 642, 849). …”
Section: General Characteristics Of Ischemia/reperfusionmentioning
confidence: 99%
“…What is not known is whether this intervention can protect the immature heart. This issue is further complicated by the fact that unlike adult heart, the vulnerability of postnatal hearts to I/R changes during development and follows a triphasic pattern in rats with 1 and 14–21 days old being most resistant to I/R injury [ 12 , 13 , 14 , 15 ]. Clinical research has also shown developmentally-related differences in cardiac vulnerability to cardiac I/R in patients undergoing open heart surgery [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of these processes accommodate the shift from a hypoxic in utero environ to a normoxic ex utero one. However, the precise mechanisms behind this varying resistance to oxygen deprivation in neonatal myocardium have still not been clearly defined [ 47 , 48 ].…”
Section: Reoxygenation and Reperfusion Injury: Animal And Clinicalmentioning
confidence: 99%
“…Cyanosis, chronic hypoxia, remains the most common preoperative physiological stress in paediatric cardiac patients [ 1 , 49 ] as well as the single largest cause of mortality [ 47 , 48 ]. In the clinical setting, it seems as though patients with cyanotic congenital heart defects have severely diminished myocardial protection [ 1 ], as well as persistently impaired ventricular function following corrective surgery and a higher rate of morbidity and mortality compared to nonhypoxaemic patients [ 50 52 ].…”
Section: Reoxygenation and Reperfusion Injury: Animal And Clinicalmentioning
confidence: 99%